2022
DOI: 10.1155/2022/8036763
|View full text |Cite|
|
Sign up to set email alerts
|

Postoperative Adjuvant Chemoradiotherapy on the Survival of Stage III Gastric Cancer

Abstract: Objective. Although adjuvant therapy has been shown to be beneficial in gastric cancer, the use of adjuvant chemoradiotherapy remains controversial. This paper investigated the effects of postoperative adjuvant chemoradiotherapy on the survival of patients with stage III gastric cancer. Methods. In total, the data of 72 stage III gastric cancer patients treated at our hospital from January 2014 to December 2019 were retrieved and assessed. They were categorized into a chemotherapy group (CT group) and a radioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%